2010
DOI: 10.1083/jcb.200911018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of exosome secretion by Rab35 and its GTPase-activating proteins TBC1D10A–C

Abstract: Oligodendrocytes secrete vesicles into the extracellular space, where they might play a role in neuron–glia communication. These exosomes are small vesicles with a diameter of 50–100 nm that are formed within multivesicular bodies and are released after fusion with the plasma membrane. The intracellular pathways that generate exosomes are poorly defined. Because Rab family guanosine triphosphatases (GTPases) together with their regulators are important membrane trafficking organizers, we investigated which Rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
588
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(601 citation statements)
references
References 46 publications
(81 reference statements)
9
588
0
4
Order By: Relevance
“…A study found that the overexpression of PLD2 led to twice the number of exosomes released from the cells while the knockdown of PLD2 led to twice the amount lower than exosomes released [65]. Another component of the EV biogenesis that could be of interest is the multivesicular body fusion with the plasma membrane and its regulatory molecules such as the Rab protein family along with their GTPases [66]. The Rab GTPases are known for their roles in membrane trafficking activity, which are part of the endosomal system.…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…A study found that the overexpression of PLD2 led to twice the number of exosomes released from the cells while the knockdown of PLD2 led to twice the amount lower than exosomes released [65]. Another component of the EV biogenesis that could be of interest is the multivesicular body fusion with the plasma membrane and its regulatory molecules such as the Rab protein family along with their GTPases [66]. The Rab GTPases are known for their roles in membrane trafficking activity, which are part of the endosomal system.…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…Proteins mediating exosome biogenesis can themselves be released on exosomes as reported for Rab35, Syntenin, and Flotillin-1 (23,26,36). We thus focused on exosome components found in human urine (15) and tested their requirements for GPRC5B-HA exosomal release by knocking down their expression using small interfering RNA (siRNA).…”
Section: An Rnai Candidate-based Screen For Regulators Of Exosomalmentioning
confidence: 99%
“…To address this issue, we investigated intracellular vesicle trafficking of the orphan G-protein-coupled receptor GPRC5B as a model exosome cargo protein (18). Although GPRC5B proteins are released in exosomes via a pathway relying on the GTPase activity of the exosome release regulator Rab35 (18,26), a substantial fraction of GPRC5B proteins are also released in microvesicles along with other known exosome cargo proteins (18), complicating the mechanistic understanding of GPRC5B exosome loading. To circumvent this promiscuity, we focused our investigation on the early intracellular trafficking events of newly synthesized GPRC5B proteins.…”
mentioning
confidence: 99%
“…ESCRT is involved in the process of membrane invagination to the formation of ILVs and in the selection of proteins integrating these vesicles. 34 Concerning ESCRT-independent signals that regulate exosomes secretion we can name the ceramide pathway, 35 intracellular Ca 2C levels, 36 p53 status, 37 Rab protein family, 38,39 Syndecan-Syntenin-ALIX proteins, 40 high level of heparanase 41 and pH. 42 How the exosome penetrates into the recipient cell is still a debated issue.…”
Section: Biogenesismentioning
confidence: 99%